The Effects of Drilling Parameters on Delamination in the Machining Process of Carbon-Reinforced Thermoplastic Polymer Composite Used in the Automotive Industry - Kondo, Marcel Yuzo [UNESP]; Callisaya, Emanuele Schneider [UNESP]; Botelho, Edson Cocchieri [UNESP]; Costa, Michelle Leali [UNESP]; de Sampaio Alves, Manoel Cleber [UNESP]; Ribeiro, Marcos Valério [UNESP] (Springer Nature, 2024)
One of the technological challenges in manufacturing components in polymeric composite materials reinforced with carbon fibers is the occurrence of delamination during the drilling process of the parts. Drilling of composite material is a widely used process in the energy, aviation, and automobilist industries since most pieces are assembled by riveting or screwing, and delamination is the factor with the most significant rejection in terms of hole quality, accounting for 60% of all parts rejected due to non-compliance issues. This study aims to find the influence of cutting speed and feed rate in the occurrence of defects in the drilling of the thermoplastic matrix composite of polyamide 6 reinforced with carbon fibers. Two different tools were used: a carbide twist drill and another diamond-coated twist tool. A full factorial matrix was used with cutting speed (40.90, 90.01, and 113.12 m/min) and three feed levels (0.018, 0.050, and 0.081 mm/rev). Machining potency, thrust force, and vibration were acquired during the drilling process, analyzed, and correlated with the hole delamination factor. The delamination behavior on the hole’s entrance and exit are different and affected differently by cutting parameters, which push-out delamination on the hole’s exit has been more critical. The found parameters to reduce delamination are Vc = 40.90 m/min, f = 0.081 mm/rev, and PCD-coated carbide tool, which indicates that thermal damage is more prominent than mechanical damage. Machining potency and thrust force correlate with the delamination factor, meaning potential signals for monitoring delamination in the PA6-based carbon-reinforced composite drilling process.